2006
DOI: 10.1136/thx.2005.051029
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia is associated with poor outcomes in patients admitted to hospital with acute exacerbations of chronic obstructive pulmonary disease

Abstract: Background: Hyperglycaemia is associated with poor outcomes from pneumonia, myocardial infarction and stroke, but the effect of blood glucose on outcomes from acute exacerbations of chronic obstructive pulmonary disease (AECOPD) has not been established. Recent UK guidelines do not comment on measurement or control of blood glucose in AECOPD. A study was therefore undertaken to determine the relationship between blood glucose concentrations, length of stay in hospital, and mortality in patients admitted with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
266
6
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(295 citation statements)
references
References 31 publications
9
266
6
14
Order By: Relevance
“…The thesis of the protective potential of a higher body mass index in diabetic patients has been discussed by MCGHAN et al [32], but is still speculative. Another explanation model is that comorbidities may include unidentified treatment options which in diabetes therapy might lead to less blood sugar escalation caused by systemic corticosteroid therapy considered harmful in the studies of BAKER et al [34] and CHAKRABARTI et al [35].…”
Section: Discussionmentioning
confidence: 99%
“…The thesis of the protective potential of a higher body mass index in diabetic patients has been discussed by MCGHAN et al [32], but is still speculative. Another explanation model is that comorbidities may include unidentified treatment options which in diabetes therapy might lead to less blood sugar escalation caused by systemic corticosteroid therapy considered harmful in the studies of BAKER et al [34] and CHAKRABARTI et al [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia during acute exacerbations of COPD requiring hospitalization is associated with poorer outcomes in terms of outcome of acute noninvasive ventilation [62], longer inpatient stay and in-hospital mortality [63]. These patients were also likely to have more than one species of bacteria grown from sputum during the admission, raising the possibility of a poorer immune response.…”
Section: Type II Diabetes Mellitusmentioning
confidence: 99%
“…2 Observational studies have shown that hyperglycemia in hospitalized patients is associated with adverse outcomes including infectious complications, increased length of stay, and increased mortality. [2][3][4][5][6][7] Recent randomized controlled trials have demonstrated that aggressive treatment of inpatient hyperglycemia improves outcomes in surgical and medical intensive care units. 8,9 Based on the available data, the American Diabetes Association (ADA) now advocates good metabolic control, defined as preprandial glucose levels of 90 to 130 mg/dL and peak postprandial glucose levels <180 mg/dL in hospitalized non-intensive care unit (ICU) patients.…”
mentioning
confidence: 99%